Boron‐Based Inhibitors of Acyl Protein Thioesterases 1 and 2. Issue 1 (13th December 2012) - Zimmermann, Tobias J.; Bürger, Marco; Tashiro, Etsu; Kondoh, Yasumitsu; Martinez, Nancy E.; Görmer, Kristina; Rosin‐Steiner, Sigrid; Shimizu, Takeshi; Ozaki, Shoichiro; Mikoshiba, Katsuhiko; Watanabe, Nobumoto; Hall, Dennis; et al.
Abstract Ras proteins are of importance in cell proliferation, and hence their mutated forms play causative roles in many kinds of cancer in different tissues. Inhibition of the Ras‐depalmitoylating enzyme acyl protein thioesterases APT1 and ‐2 is a new approach to modulating the Ras cycle. Here we present boronic and borinic acid derivatives as a new class of potent and nontoxic APT inhibitors. These compounds were detected by extensive library screening using chemical arrays and turned out to inhibit human APT1 and ‐2 in a competitive mode. Furthermore, one of the molecules was demonstrated to inhibit Erk1/2 phosphorylation significantly.